2000
DOI: 10.1037/0022-006x.68.3.451
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of change in multisystemic therapy: Reducing delinquent behavior through therapist adherence and improved family and peer functioning.

Abstract: The mechanisms through which multisystemic therapy (MST) decreased delinquent behavior were assessed in 2 samples of juvenile offenders. Sample 1 included serious offenders who were predominantly rural, male, and African American. Sample 2 included substance-abusing offenders who were predominantly urban, male, and Caucasian. Therapist adherence to the MST protocol (based on multiple respondents) was associated with improved family relations (family cohesion, family functioning, and parent monitoring) and decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
310
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 398 publications
(336 citation statements)
references
References 71 publications
(92 reference statements)
24
310
0
2
Order By: Relevance
“…Studies indicate that family members, particularly parents, are instrumental in facilitating the adolescent's change process (Huey, Henggeler, Brondino, & Pickrel, 2000;Schmidt, Liddle, & Dakof, 1996).…”
Section: Preventing Dropout In Family Therapymentioning
confidence: 99%
“…Studies indicate that family members, particularly parents, are instrumental in facilitating the adolescent's change process (Huey, Henggeler, Brondino, & Pickrel, 2000;Schmidt, Liddle, & Dakof, 1996).…”
Section: Preventing Dropout In Family Therapymentioning
confidence: 99%
“…Several studies have found that therapist adherence to the treatment protocol is an important predictor of clinical outcomes, especially when studies are conducted in community settings (Henggeler et al, 1999;Hogue et al, 2008;Huey et al, 2000;Schoenwald et al, 2000). Despite its importance, there is a lack of research regarding the role of treatment adherence in successful community replications of efficacious family-based programs.…”
Section: Nih Public Accessmentioning
confidence: 99%
“…Treatment fidelity is most often defined as therapist adherence, or the degree to which a given therapy is implemented in accordance with essential theoretical and procedural aspects of the model (Hogue et al, 2006; Waltz, Addis, Koerner, & Jacobson, 1993). In a few cases, treatment adherence has also been linked to treatment outcomes in family-based therapies (Henggeler et al, 1999;Huey et al, 2000;Schoenwald, Henggeler, Brondino & Rowland, 2000). However, treatment adherence may not always be related to better outcomes.…”
mentioning
confidence: 99%
“…Moreover, family involvement may be essential to successful medication adherence and treatment retention with some specialized populations, including adolescents (Huey et al, 2000). Weaknesses include limited generalizability, in that studies which require the involvement of significant others will necessarily be limited to the subset of patients who have comparatively strong social supports and family members who are willing to participate in treatment.…”
Section: Family and Couples Approachesmentioning
confidence: 99%